Perancangan alat uji roda gigi menggunakan metode VDI 2221 - Cupu, Dedi Rosa Putra; Afrizala, Efi; Kalduma, Ibnu (Prosiding SNTTM, 2023)
The transmission system is vital in automotive and industrial applications, including gears. Gears are the most widely transmission components used to transmit the power and rotational speed from the driver component to others. Power is transmitted by contact rolling between two contacting gear surfaces. The contacting area is relatively tiny enough to transmit very high power, resulting in high pressure on the contact surface of the gears. This causes failure on the gear surface, such as pitting and scuffing. To investigate the failures and their causes, a gear test rig is utilized, and this work aims to design a gear test rig using the VDI 2221 method. VDI 2221 is used due to its efficient and systematic design method from the product concept variants. Calculation and design of the components referred to Kiyokatsu Suga and Sularso. Static structural analysis was conducted to determine the strength and safety of the designed gear test. This study's result is a gear test rig design with a maximum von Mises stress of 19.47 MPa at the main frame. Then, a dynamic simulation was carried out, and this designed gear test rig produced a friction coefficient of 0.342.